2013
DOI: 10.1186/1556-276x-8-349
|View full text |Cite
|
Sign up to set email alerts
|

Uniform SiGe/Si quantum well nanorod and nanodot arrays fabricated using nanosphere lithography

Abstract: This study fabricates the optically active uniform SiGe/Si multiple quantum well (MQW) nanorod and nanodot arrays from the Si0.4Ge0.6/Si MQWs using nanosphere lithography (NSL) combined with the reactive ion etching (RIE) process. Compared to the as-grown sample, we observe an obvious blueshift in photoluminescence (PL) spectra for the SiGe/Si MQW nanorod and nanodot arrays, which can be attributed to the transition of PL emission from the upper multiple quantum dot-like SiGe layers to the lower MQWs. A possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…As we know, the penetration depths of the 488-nm line of the Ar+ laser in Ge and Si are about 16 and 400 nm, respectively [ 15 , 22 ]. For the as-grown GeSi MQW sample, most electron-hole (e-h) pairs are generated in the top Si layer and the upper GeSi QW regions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we know, the penetration depths of the 488-nm line of the Ar+ laser in Ge and Si are about 16 and 400 nm, respectively [ 15 , 22 ]. For the as-grown GeSi MQW sample, most electron-hole (e-h) pairs are generated in the top Si layer and the upper GeSi QW regions.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al also observed PL emission enhancement in size-uncontrollable Si/Ge superlattice pyramidal nanodots, which were fabricated by chemical selective etching through a self-assembled Ge QD mask [ 14 ]. Recently, Chang et al successfully fabricated ordered SiGe/Si MQW nanorod and nanodot arrays with different heights by combining nanosphere lithography and reactive ion-etching (RIE) process [ 15 ]. However, in the PL spectra, the intensity of the Si/Ge MQW nanorod and nanodot array nanostructure samples did not increase significantly.…”
Section: Introductionmentioning
confidence: 99%
“…With this method it is complicated to control the shape and composition of the SiGe micro/nanostructures. [5][6][7][8] (ii) Fabrication by a top-down approach, such as wet etching, [9] reactive ion etching, [10][11][12] ion beam etching [13] or metal-assisted chemical etching. [14] Of the above methods, laser irradiation is an easy to operate technology that has a rapid and localized energy process together with a wide range of tenability.…”
Section: Introductionmentioning
confidence: 99%
“…Polystyrene (PS) nanospheres have been attracting great attention from several research fields due to their ability for fabricating novel nanomaterials and nanostructures, such as ordered nanowire arrays [ 1 3 ], nanopillar arrays [ 4 , 5 ], nanohole arrays [ 6 , 7 ], nanodot arrays [ 8 ], core/shell composite materials [ 9 , 10 ], nanomesh [ 11 , 12 ], and magnetic quantum dots [ 13 ]. Particularly, nanosphere lithography has been one of the most popular research hotspots in designing the ordered nanostructure arrays since it takes the advantages of simpler process and lower cost.…”
Section: Introductionmentioning
confidence: 99%